Hilar/mediastinal and cutaneous drug-induced sarcoidosis-like reaction associated with immune checkpoint inhibitors in metastatic colorectal cancer: a case report - Sagawa, Tamotsu; Sato, Yasushi; Nagashima, Hiroyuki; Takada, Kohichi; Takahashi, Mamoru; Hirakawa, Masahiro; Hamaguchi, Kyoko; Tamura, Fumito; Fujikawa, Koshi; Okamoto, Koichi; Kawano, Yutaka; Sogabe, Masahiro; et al. (Frontiers in Immunology, 2023)
Background Immune checkpoint inhibitors (ICIs) are the standard treatment for metastatic colorectal cancer (mCRC) with high microsatellite instability (MSI-H). Among immune-related adverse events (irAEs), drug-induced sarcoidosis-like reactions (DISR) are often difficult to differentiate from cancer progression. Main Body This is a case of a woman in her mid-60s, with mCRC (RAS wild/BRAF mutant/MSI-H) and abdominal lymph node metastasis, treated with four courses of ipilimumab + nivolumab every 3 weeks, followed by nivolumab every 2 weeks as third-line treatment. After treatment, the original lymph node metastases shrank, but hilar/mediastinal lymph nodes appeared. Endoscopic ultrasound-guided fine-needle aspiration of these lymph nodes revealed multiple epithelioid granulomas without necrosis, indicating a sarcoidosis-like reaction. Fluorodeoxyglucose-positron emission tomography scan showed abnormal subcutaneous accumulation in bilateral forearms and bilateral knee joints. Biopsy of the cutaneous lesions was also performed, which revealed epithelioid granulomas. As the patient had no symptoms in other organs, no specific therapeutic intervention was administered. After the discontinuation of immunotherapy, the sarcoidosis-like reaction regressed without cancer relapse. Conclusions Clinicians should be aware of the possibility of DISR as an irAE during the ICI treatment of mCRC. In suspected cases of DISR following ICI therapy, it is important to differentiate between cancer progression and DISR through histological diagnosis for the subsequent strategy, as radiological and serological findings are not definitive.